VD_FINDINFO HC / 2012 / 199 vom 20. März 2012 - VD Tribunal cantonal (2012)
SOMMATION, RÉSILIATION, PRINCIPE DE LA RÉCEPTION, DISTRIBUTION DU COURRIER, COURRIER A | 257d CO, 106 al. 1 CPC (CH), 308 CPC (CH), 310 CPC (CH), 314 al. 1 CPC (CH), 92 al. 1 CPC (CH)